Communication Plans in the Spanish University - Pellicer Jordá, María Teresa (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2021)
Communication is fundamental in the global society and it is essential that all organizations, whether public or private, have a communication plan, a roadmap of their communication actions, which allows them to establish a good design, a clear strategy, control mechanisms and evaluation of the actions carried out. In the case of Spanish universities a very few of them have a text of this type. This article aims to carry out a diagnosis of the situation, as well as a theoretical review of the advantages offered by having a communication plan, which detects the strengths and weaknesses and establishes concrete improvement actions, organized over time with a schedule, and with a forecast of the resources necessary to carry them out. The results show that only five of the 84 Spanish universities have a public communication plan, which represents 5.9% of all universities and only two of them offer mechanisms to control compliance with the proposed actions. This analysis also allows us to know which are the main objectives and parameters relevant to these universities in the matter of communication, establish a critical review of them and design a communication plan scheme that could be the basis for any text of this type that want to perform. The general diagnosis that we can arrive at based on the data analyzed is that there is much to be done on communication issues in Spanish universities.